2014
DOI: 10.1007/s13277-014-2402-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 inhibits cellular proliferation and invasion by targeting Ets-1 in breast cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that, by targeting certain messenger RNAs (mRNAs) for translational repression or cleavage, can regulate the expression of these genes. In addition, miRNAs may also function as oncogenes and tumor-suppressor genes, as the abnormal expression of miRNAs is associated with various human tumors. However, the effects of the expression of miR-124 in breast cancer remain unclear. The present study was conducted to study the expression of miR-124 in breast cancer, paying pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…It has also been reported to function as an important regulator of many human cancers (43,44). In particular, recent studies have indicated that miR-124 targets specific genes to regulate proliferation and migration in breast cancer (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported to function as an important regulator of many human cancers (43,44). In particular, recent studies have indicated that miR-124 targets specific genes to regulate proliferation and migration in breast cancer (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are short (approximately 22 bases) noncoding RNA molecules that post-transcriptionally regulate gene expression through incomplete base pairing with the 3′ UTR of target mRNAs [15]. They have been estimated to regulate up to 30% of all human genes and to control a variety of cellular processes [48]. In IgAN, there are few reports about the regulation of miRNAs in mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…They act as negative regulators of gene expression and play a crucial role in regulating breast cancer cell proliferation, invasion, migration and metastasis [5][6][7]. Accumulating data showed a number of miRNAs, such as miR-23 [8], miR-200 [9], miR-378 [10] were reported as key regulators in breast cancer.…”
Section: Introductionmentioning
confidence: 99%